IMPLEMENTASI PENDEKATAN DEEP LEARNING MELALUI PROBLEM BASED LEARNING BERBANTU GOOGLE SITES UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA (JURNAL ILMIAH TUT WURI HANDAYANI, 2024)
This study aims to determine the extent to which the Deep Learning approach through Problem Based Learning assisted by Google Sites is able to encourage in-depth understanding, critical thinking, and better problem solving skills to improve student learning achievement in class XII of SMK N 1 Nanggulan. This study was designed through a case study to explore the application of IT-integrated deep learning in Google Sites. Data sources consisted of teachers, and students who had direct experience in this method, selected through the planning, action, observation, and reflection stages. Data collection techniques used observation, documentation, test instruments. The instruments used were observation, guidelines, interviews, and learning outcome tests. The study was declared successful if students' in-depth understanding, critical thinking, and active ability provided student learning outcomes. The analysis technique used descriptive analysis. The study findings showed that the Deep Learning Problem Based Learning model was able to improve conceptual understanding, critical thinking skills, and student creativity. It has also been proven that the application of this method through using the Problem Based Learning model assisted by Google Sites can increase student active involvement, resulting in an increase in student learning outcomes.